Developing Instruments to Measure Student's Creative Thinking Skills in Vocational Schools - Agung Dalyanto; Sajidan Sajidan; Siswandari Siswandari; Sukarmin Sukarmin (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
Introduction: Learning activities require creative thinking skills in supporting sustainable development. Instruments that measure the creative thinking skills of vocational school students are still very limited. Purpose: Thisarticle aims to develop and validate instruments in measuring the creative thinking skills of vocational school students. Methods: Research data obtained through tests of creative thinking skills based on sustainable development. Item analysis to determine the internal consistency criteria used Pearson Product Moment on data collected from thirty-five students. The instrument consists of a verbal test (28 questions) and a figural test (2 questions) in measuring the components of fluency, flexibility, originality, and elaboration. Instrument reliability was determined using the Cronbachalpha coefficient. Result: The internal consistency criteria of each component is relatively high. The lowest average degree was 0.536 for the flexibility component, and the highest average degree was 0.727 for the fluency component. The Cronbach alpha coefficient for the reliability test was 0.723. Conclusion: The results revealed that the instrument of creative thinking skills is a valid and reliable tool for assessing the creative thinking skills of vocational school students